Pelayanan Publik Bagi Penyandang Masalah Kesejahteraan Sosial di Dinas Sosial Kabupaten Indragiri Hilir - Yous Gunawan (STAI Hubbulwathan Duri, 2019)
Form of public service has been multifaceted, service may include goods real, goods not real, and may also be in the form of services. The government issued policy that aims to give social protection and social security. One form of the protection is is giving protection and service for people with social welfare problems. The purpose of this research is to know picture people with social welfare problems that develops in the kabupaten indragiri hilir; the efforts being done by the agency social and labor District Indragiri Hilir in giving public service to residents people with social welfare problems and the factors that affect the implementation of the public service to people with social welfare problems in District Indragiri Hilir.This research research using qualitative approach with instrument research in-depth interviews so the handling can be known on the community people with social welfare problems had been conducted by the district government Indragiri Hilir. The type of people with social welfare problems in the district of Indragiri Hilir, that as many as 28 type and totaled 41.915 people. In in search of solutions to the problems people with social welfare problems in in providing services based on justice, empowerment that encourages self-reliance, and development that create wealth has not been applied in an optimum manner, because of the number of problems and limitations, among them the limited funds, the number of people with social welfare problems that change and grow, government officials resources limited, there has been no public awareness and the private sector to handle problems together people with social welfare problems